PROSES MANUFAKTUR MESIN PENCACAH (CHOPPER) PAKAN TERNAK - Luthfi Dzaki Rizaldi Darmawan, (2022)
Technology is something that will continue to develop to help humans do a job. Technology that can make it easier for farmers to provide feed, namely an animal feed chopper. This is what we will try to implement in Gunung Kidul, precisely in the district. Ngilpar, Dungsuru Village. There the majority of livestock feed is still the traditional way such as sickles. The machine is designed to help farmers in carrying out the enumeration process effectively and efficiently. For animal feed, it is not only in the form of grass but also mixes other ingredients such as corn, straw, and others in order to save costs. The machine for chopping food for livestock consists of a gasoline motor that functions as a propulsion, casing, blade, power transmission system, and frame. This study uses literature techniques to collect concepts and data used in research obtained from various sources or previous research. After research on the manufacturing process of the animal feed chopper, it is proven that it can chop as much as 45 kg/hour and produce chops with a length of 0.5-5 cm which are suitable for animal feed. The time required for machining the animal feed chopper is 6,331 hours and the required fabrication cost is Rp 2,617,439.46.